Developing a Virtual Museum Tour as a History Learning Medium for Junior High Schools - Muhammad Rijal Fitri Hidayatullah; Eka Budhi Santosa; Riris Fityatun Nur Faizah (Universitas Sebelas Maret, 2026)
History instruction at the junior secondary school level remains predominantly teacher-centered and expository, limiting students’ active engagement and conceptual understanding. This study aims to develop a Virtual Museum Tour–based learning media using the Lapentor platform for seventh-grade prehistory materials and to examine its feasibility through expert validation. The research employed a Research and Development (R&D) approach based on the Alessi & Trollip development model, which consists of planning, design, and development stages. The research participants were seventh-grade students of SMP Widya Wacana 1 Surakarta. Data were collected through observation, interviews, documentation, and validation questionnaires administered to media and subject-matter experts. The results indicate that the Virtual Museum Tour media, designed in accordance with the Cognitive Theory of Multimedia Learning proposed by Richard E. Mayer, meets the feasibility criteria in terms of content accuracy, visual design, navigation, and multimedia integration. The developed product was deemed valid and suitable for use as a visual-interactive alternative in history instruction.